Self-Care of Patients Undergoing Hemodialysis in Compliance with Diet Nutrition and Fluids - Mardiyah, Adiyati; Maktum, Ummi; Julianti, Erna; Zulkifli, Zulkifli (Chakra Brahmanda Lentera Institute, 2024)
Background: Hemodialysis accompanied by proper management of nutritional and fluid diet is very important, as excessive fluid intake can worsen the condition of patients with chronic kidney disease. The aim of research to know about Self Care of Patients Undergoing Hemodialysis in Compliance with Diet Nutrition and Fluids Methods: This study is a quantitative study, this type of research is descriptive that describes self-care in hemodialysis patients in adherence to nutritional and fluid diets. This study uses a cross sectional design. This design looks at the picture of self-care, nutrient and fluid diet compliance. Sampling in this study used purposive sampling. A total sample of 118 respondents. Results: Most of the patients in the category of non-compliance with hemodialysis in the diet of nutrients and fluids from all questionnaire items (asmaul husna) were 81 respondents (68.6%). Conclusion: Patients can understand the importance of self-way, nutritional diet and high-quality health to improve health pasien. It is recommended to implement comprehensive educational programs for patients on the importance of adhering to dietary and fluid restrictions, as well as self-management techniques, to enhance their overall health outcomes.